The Modulatory effects of Methanolic Stem Bark Extract of Acacia Nilotica on Serum Level of CA 15-3, Liver and Kidney Biomarkers in Alloxan Induced Type-1 Diabetic WistarRats - 1 1 2 3 Alhassan, Hussaini Mohammed , Isah Sumayya Hamzat , Usman Malami Aliyu , Zafaru Muhammad Bunza , 1 1 4 (Sokoto Journal of Medical Laboratory Science)
The use of natural products as a means of treatment for many physiological threats such as diabetes is currently gaining momentum in Nigeria. Diabetes is ametabolic syndrome that afflicts an estimate of 433 million people and defects in liver function, kidney function and emergence of cancer are some of its complications. Hence this study was designed to evaluate the effect of Acacia nilotica on the Serum Level of CA 15-3, Liver and kidney function in Alloxan-induced type | diabetic Wistar Rats. A total of 28 rats were used in the study. Twenty-four (24) Rats of either gender was induced with 160mg/kg body weight of alloxan and left to develop diabetes for 72 hours after which there were divided into seven groups of four rats each: Group I: Normal Control, Group II: Diabetic Control, Group III, IV and V represent Diabetic rats treated with stem bark extract of Acacia nilotica (300mg, 600mg and 1200mg respectively). Group VI and VII represent Diabetic Rats treated with 250mg of metformin and 600mg of Acacia nilotica extract + 150mg of metformin respectively. The treatment was conducted for 14 days. At the end of the experiment, rats were fasted overnight and sacrificed. The blood samples were collected under chloroform anesthesia for the evaluation of liverand kidney biomarkers. The results indicated a statistically significant (p<0.05) increase in kidney and liver function parameters in diabetic rats when compared to normal rats except potassium, Total protein, albumin and direct bilirubin that were still normal. These findings indicate that Acacia nolotica possesses both renal and hepatoprotective effects on the kidney and liver. Further investigations should be conducted to elucidate the underlying mechanisms by which Acacia nilotica exerts these effects.